The Effectiveness of Virtual Reality in Individual Counseling to Enhance Public Speaking Skills: A Study among 7th Graders - Oktariani, Firda Nova; Prihandoko, Tri Leksono; Dewi, Widya Novi Angga (citeus, 2025)
Improving public speaking skills is necessary to help students build self-confidence, enhance communication skills, and support their education and careers. This research uses a qualitative method where the researcher is the key instrument, with purposive sampling of data sources and triangulation techniques for data collection. The study finds that: (1) The use of Virtual Reality (VR) during individual counseling for middle school students significantly aids in improving public speaking skills, as evidenced by the change from 0% in initial observations of public speaking skills before VR counseling to 75% after VR counseling, and from 8.3% to 66.6% in the second client. (2) VR counseling impacts students by boosting their public speaking skills and encouraging them to improve academically and non-academically. (3) VR counseling proves to enhance public speaking abilities in terms of verbal communication, vocal control, and visual expression, with students demonstrating clearer language and structure, better volume regulation, and improved self-expression in public.